MYOCARDIUM PROTECTIVE FUNCTION OF SALVIANOLIC ACID B IN ISCHEMIA REPERFUSION RATS - Qiao, Zengyong; Xu, Yawei (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Salvia miltiorrhiza (SM) Bunge is one of the widely-used Chinese medicinal herbs. Salvianolic acid B (Sal B), abioactive compound isolated from the Chinese herb Radix Salviae Miltiorrhizae, has been reported to exhibit anti-inflammatory andanti-oxidantive effects.Material and method: To study the cardioprotective effects of salvianolic acid B (Sal B) on acute myocardial ischemia reperfusion(MIR) injury rats, on the basis of this investigation, the possible mechanism of salvianolic acid B was elucidated. Male Sprague-Dawley rats (200–220 g) were randomly divided into five groups: sham-operated, MIR, MIR + Sal B (10 mg/kg/day, orally), MIR +Sal B (20 mg/kg/day, orally) and MIR + Sal B (30 mg/kg/day, orally). Before operation, the foregoing groups were pretreated withhomologous drug once a day for 7 days, respectively. After twelve hours in MIR, the cardioprotective effects of SPJ were evaluatedby infarct size, biochemical values, and the antioxidative and antiapoptotic relative gene expressions.Results: Sal B significantly improved heart function and decreased infarct size; remarkably decreased levels of serum TNF-α andIL-1β levels, increased contents of myocardium antioxidant enzymes activities; western blot results showed that Sal B ameliorate theincreased Bax and caspase-3 protins expressions and decreased Bcl-2 proteins expression and ratios of Bcl-2 to Bax.Conclusion: In ischemic myocardium, oxidative stress caused the overgeneration and accumulation of reactive oxygen species(ROS), which was central of cardiac ischemic injury. Sal B exerted beneficially cardioprotective effects on myocardial ischemiainjury rats, mainly scavenging oxidative stress-triggered overgeneration and accumulation of ROS, alleviating myocardial ischemiainjury and cardiac cell death.